New Technological Approach for the Evaluation of Postural Control Abilities in Children with Developmental Coordination Disorder - Giada Martini; Elena Beani; Silvia Filogna; Valentina Menici; Giovanni Cioni; Roberta Battini; Giuseppina Sgandurra (MDPI AG, 2022)
Background: Developmental Coordination Disorder (DCD) causes difficulties in postural control which are crucial to assess due to their impact on everyday life. There is a lack of suitable tools to acquire quantitative data and deeply analyze postural control, especially during the developmental age. The aim of this study is to investigate postural control skills in children with DCD and typically developing children (TD) using the Virtual Reality Rehabilitation System (VRRS). Methods: 18 children with DCD and 30 TD children (mean age 9.12 ± 2.65 and 7.12 ± 2.77 years, respectively) were tested by using the Movement Assessment Battery for Children Second Edition (MABC-2) and a VRRS stabilometric balance platform. A t-test was performed to identify differences in the VRRS parameters between the two groups. Furthermore, we investigated whether a correlation exists between the VRRS data and the MABC-2. Results: Significant differences (p < 0.05) in mean distance and frequency of the COP are found in the two groups. These parameters also correlate with the MABC-2 total score (p ≤ 0.05) and balance subscales (p ≤ 0.05). Conclusions: This study opens a new frontier for the assessment of postural skills in children with DCD and represents a potential basis for a tailored rehabilitation program, from which their postural stability and, consequently, their everyday life will benefit.